The initiation of labour at term gestation: Physiology and practice implications. (August 2020) - Hundley, Vanora; Downe, Soo; Buckley, Sarah J.
Abstract: Little is known about the physiology of labour onset at term, and there is a debate about what signs and symptoms should be used to define it. In low resource settings, particularly for remote and rural communities, delay in recognising labour onset may mean a delay in seeking a skilled birth attendant. This chapter presents the most recent evidence about the physiology of labour onset, including the complex neuro-hormonal, biophysical, psychological and emotional factors that contribute. The symptoms of labour onset are explored from the perspective of both pregnant women and service providers in a range of sociocultural contexts. Early labour presents challenges for pregnant women, their families, communities and health care professionals. The chapter discusses how maternity care services should be designed, and delivered to ensure that women get the optimum advice and care at the beginning of labour. Highlights: Complex neurohormonal, biophysical, psychological, and emotional factors contribute to labour onset. There is a debate about what signs and symptoms should be used to define labour onset. Early labour presents challenges for pregnant women and health care professionals. Hospital admission before active labour results in a cascade of unnecessary intervention. Optimal maternity care requires an understanding of women's experiences of early labour.